Recent Insights from Computational Materials Chemistry into Interfaces Relevant to Enhanced Oil Recovery. Issue 4 (5th February 2019) - Singh, Nirpendra; Sharma, Sitansh; Vovusha, Hakkim; Li, Huifang; Schwingenschlögl, Udo
Abstract: Efficient usage of earth's limited oil reserves requires fundamental understanding of the interfacial effects governing oil recovery. As experimental access to such knowledge is often limited, modern simulation techniques are constantly gaining relevance in this field of research. This progress report therefore addresses recent studies of materials chemistry dealing with computational approaches to obtain insights into the interaction between rock surfaces, water, and oil components. It aims both at providing a starting point for newcomers to the field and at equipping experts with an overview of new developments. Being the most prominent mineral in oil reservoirs and the main component of sedimentary carbonate rock, special attention is given to interfaces involving calcite (CaCO3 ). While the research field still develops in two branches with most studies dealing either with rock–water or rock–oil interaction, it will be important to consider also collective effects at general rock–water–oil interfaces in future investigations. Abstract : Computational approaches to obtain insights into the interaction between rock surfaces, water, and oil components are addressed in this review. It aims both at providing a starting point for newcomers to the field and at equipping experts with an overview of new developments